Sztuka i państwo – refleksje na marginesie "Wolnego wyboru" Miltona i Rose Friedman - Tendera, Paulina; Rubiś, Wojciech (Hybris, 2017)
In this article we reflect on the relationship between the state and the contemporary art world. We show the errors that occur in the politics of art financed from public funds. Our authority are Milton and Rose Friedman and their book Free to choose.